2007
DOI: 10.1210/en.2006-1709
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized Low-Density Lipoprotein Stimulates p53-Dependent Activation of Proapoptotic Bax Leading to Apoptosis of Differentiated Endothelial Progenitor Cells

Abstract: Dyslipidemia increases the risks for atherosclerosis in part by impairing endothelial integrity; endothelial progenitor cells (EPCs) play a pivotal role in reendothelialization. In this study, we investigated the mechanism whereby oxidized low-density lipoprotein (oxLDL) affects the function of differentiated EPCs (EDCs). In EDCs expanded in vitro from EPCs isolated from human cord blood, we measured EDC responses to both copper-oxidized LDL and L5, an electronegative LDL minimally oxidized in vivo in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 47 publications
2
57
0
1
Order By: Relevance
“…Some data have indicated the possibility of p53-dependent apoptosis induced by oxidatively modified LDL due to the release of reactive oxygen species (ROS) by disrupted mitochondria [6]. Thus, the mechanism underlying the triggering of apoptosis in cells by HOCl-modified phosphatidylcholines may be similar to that found for oxLDL.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Some data have indicated the possibility of p53-dependent apoptosis induced by oxidatively modified LDL due to the release of reactive oxygen species (ROS) by disrupted mitochondria [6]. Thus, the mechanism underlying the triggering of apoptosis in cells by HOCl-modified phosphatidylcholines may be similar to that found for oxLDL.…”
Section: Discussionmentioning
confidence: 95%
“…Apoptotic endothelial cells have been demonstrated to release IL-1 and adhesion molecules, as well as to have reduced production of NO and prostacyclins, leading to platelet and neutrophil activation [1]. A number of reports have suggested that oxidatively-modified low density lipoproteins (ox-LDL) are pro-apoptotic factors and can be considered as one of the many risk factors in atherosclerosis [5,6]. In particular, modifications of the protein and lipids of the LDL fraction accelerate its uptake by macrophages, resulting in conversion of these cells into foam cells [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…34,35 Not recognized widely, low-concentration oxLDL may paradoxically protect endothelial cells against apoptosis provoked by high-concentration oxLDL. 36,37 We hypothesized that very low concentrations of oxLDL which are present during physiological state may have a nonpathologic role in cell biology. As endothelial cells grow and proliferate, they tend to from tubules.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, the key players in CHD, i.e., blood monocytes, lymphocytes, endothelial cells, vascular fibroblasts, and smooth muscle cells, while engaged in the injury and repair struggle eventually giving rise to fatal plaque formation and rupture (41), might acquire fatal dysfunctions caused by diabetes-induced DNA damage. There is a wealth of detailed data on diabetes-related malfunctioning of these cells and platelets and on oxidative stress on endothelial cells in atherosclerosis (42). In addition, chromosomal alterations have been found in atherosclerotic plaques (43).…”
Section: Discussionmentioning
confidence: 99%